+0  
 
0
38
1
avatar

Consider the two expressions (6x^3 + 9x^2 + 4x + 7 - 17x^2 - 8x + 8)/(2x + 3 - 7x - 11) and 4x^2 - 7 + 1/(2x + 3 - 7x - 11)

a) Show that the two expressions represent equal numbers when x = 10

b) Explain why these two expressions do not represent equal numbers when  x = -3/2

c) Show that these two expressions represent equal numbers for all x other than  -3/2.

 Nov 30, 2022
 #1
avatar
0

First expression:  (6*10^3 + 9*10^2 + 4*10 + 7 - 17*10^2 - 8*10 + 8) / (2*10 + 3 - 7*10 - 11)== - 5175 / 58

 

2nd expression:  (4*10^2 - 7 + 1) / (2*10 + 3 - 7*10 - 11)== - 197 / 29

 

Do they look EQUAL to you ?! What have written or copied wrong? Perhaps, your brackets?

 Nov 30, 2022

2 Online Users